2021
DOI: 10.1002/hpja.531
|View full text |Cite
|
Sign up to set email alerts
|

Health halo or genuine product development: Are better‐for‐you alcohol products actually healthier?

Abstract: Alcohol plays a role in more than 200 different chronic health problems, including cardiovascular disease, at least seven types of cancer, type II diabetes, stroke, liver disease and overweight and obesity. 1 Alcoholic products are also the single biggest contributor to discretionary food intake among Australian adults, accounting for 6% of total energy intake in 2011-2012; 35% of total daily energy was consumed from discretionary foods. 2 Alcohol industry analysts have identified that Australians are becoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Although there has only been a limited number of studies investigating the impact of nutrition content claims on alcoholic beverages specifically, evidence indicates that their presence is likely to increase perceptions of the healthiness of alcohol products and can exacerbate existing low levels of understanding of alcohol's energy contribution and other health risks associated with the consumption of alcohol [28]. As such, there are indications that the presence of nutrition content claims may create a 'health halo' effect for alcohol products [27]. While more research is needed in this area, regulations restricting nutrition content claims on alcoholic beverages may be required as part of broader efforts to improve population diets and reduce alcohol-related harms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there has only been a limited number of studies investigating the impact of nutrition content claims on alcoholic beverages specifically, evidence indicates that their presence is likely to increase perceptions of the healthiness of alcohol products and can exacerbate existing low levels of understanding of alcohol's energy contribution and other health risks associated with the consumption of alcohol [28]. As such, there are indications that the presence of nutrition content claims may create a 'health halo' effect for alcohol products [27]. While more research is needed in this area, regulations restricting nutrition content claims on alcoholic beverages may be required as part of broader efforts to improve population diets and reduce alcohol-related harms.…”
Section: Discussionmentioning
confidence: 99%
“…The few existing studies in this area indicate that nutrition information can help deter consumers from purchasing alcoholic beverages, such as RTDs, that contain high amounts of 'risk nutrients' (such as sugar) but may be less effective in deterring purchases of other alcoholic beverages, like wines, with relatively lower amounts of risk nutrients [24][25][26]. As is the case with food products, research also indicates that nutrition labels can cause a halo effect with alcohol products [27]. One study indicated that alcohol products marketed as 'better-for-you' created an illusion of healthiness, despite the potential adverse impacts of the products on population health [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of evidence about how people view the marketing and availability of zero alcohol-branded products. [20][21][22]. The perspectives of people who experience alcohol-related harm are fundamental to the development of alcohol policy, and more research is needed to understand how marketing of ZAPs impacts or supports behaviour change for people experiencing alcohol dependence or in recovery.…”
Section: Future Researchmentioning
confidence: 99%
“…In the retail environment, ZAPs are sometimes grouped with other alcohol products that might include nutrition content claims such as ‘low sugar’, ‘low carbohydrate’, ‘organic’ and ‘gluten free’ [7]. Public health bodies have been critical of how alcohol products promoted as ‘better for you’ are being used to ‘healthwash’ the alcohol industry and position the products as healthier than they are [20].…”
Section: Introductionmentioning
confidence: 99%